Estimation of probable maximum precipitation at three provinces in Northeast Vietnam using historical data and future climate change scenarios - Thanh Thuy, L.; Kawagoe, S.; Sarukkalige, Priyantha (2019)
Study region: In this study, three provinces in Northeast Vietnam including Bac Kan, Thai Nguyen, and Tuyen Quang are examined to determine the precipitation variation characteristics. Study focus: The average yearly temperature during the last two decades in Northeast Vietnam has increased by 0.72 °C when compared to the period 1962–1990. The Clausius Clapeyron (CC) relation indicates that a warmer atmosphere can result in higher moisture-holding capacity; hence, there is the possibility of increased extreme rainfall with respect to the rise in temperature. We evaluate the relationship between the average 24-hour temperature and rainfall extremes using the binning method. The estimation of the 24-hour probable maximum precipitation (PMP) is then implemented based on the moisture maximization and Hershfield statistical methods. New hydrological insights for the region: The 99.9 th percentiles of 24-hour precipitation are close to the super CC scaling up to peak points of 22.6–25.6 °C and decrease at higher temperatures. The Hershfield method produces 24-hour PMP results ranging from 232 mm to 895 mm. PMP outputs using the moisture maximization method based on the 100-year dew point are higher than those results generated from the statistical method except for Chiem Hoa station. Considering possible changes in future relative humidity under a warming climate from GCMs and RCM projections for two RCP scenarios, RCP 8.5 indicates the possible rise in probable extreme precipitation.